Tourism Based on Historical Heritage in Langsa, Aceh, Indonesia - Wibowo, Guntur Arie; Rahman, Aulia; Chairuddin, Chairuddin; Majida, Andi Zulfa; Hermawan , Devi (Universitas Negeri Surabaya, 2022)
This article discusses the diversity of historical heritage found in Langsa City which has the potential to become a sustainable historical heritage. This paper also describes how to realize sustainable tourism based on history and culture and improve the quality of life of the community by utilizing historical and cultural heritage. The research was conducted in Langsa city, Aceh province, Indonesia. This study uses a qualitative approach by conducting observations, in-depth interviews, and documentation studies. Based on the findings and facts in the field, identify three potentials that can become icons for the development of historical and cultural tourism. The first is the historical heritage in the form of physical, the second is in the form of culture and the third is the historical heritage in the form of culinary. This diversity of historical heritage-based sustainable tourism has not received much attention in the study of sustainable tourism. This is because tourism infrastructure such as destinations and human resources have not been well prepared. In addition, the involvement of public participation to help realize sustainable tourism is still not optimal. Tourism by utilizing historical heritage capital is very important for the environment and society. and have an impact on the local and national economy. Realizing sustainable tourism based on historical and cultural heritage is done by implementing destination management, so that each type of tourism gets the same attention so that all tourism sectors can progress together, increase the quality of tourism, and can benefit all parties. It is also recommended to build good cooperation between the government, the community and the private sector in developing sustainable tourism based on historical and cultural heritage. Cultural heritage buildings that have received status and are being proposed by the government as cultural heritage so that their maintenance and utilization can be optimal. In addition, it is necessary to open spaces for collaboration between the government, academia and the community in the development of sustainable tourism based on historical heritage.